Factors Influencing the Purchase Decision towards Hair Color Products - Probosutejo, Michael (iBuss Management, 2013)
In the last 4 years, Indonesiaâs hair color industry has consistently grown even reaching IDR 2.75trillion in 2011â2012. This has created more intense competition within the market, in which the producers utilize various ways to attain more customers. Competing in the B-to-C class market, LâOrÃ©alâs Matrix division has just launched a new brand called So Color. It is created to replace the existing brand, So Color Beauty, which is not well sold in the market. Unfortunately, the sales of this new brand has shown a constant decrease from October to December 2012. Thus, researcher conducts this research to identify the factors influencing the purchase decision towards hair color products and thereby, to solve the problem of So Color. Gathering the primary data from 231 respondents and processing it using factor analysis, the researcher finds that there are 11 newly formed factors, which influence the purchase decision towards hair color products.Keywords: Hair Color Product, Purchase Decision, So Color, External and Internal Factors